2021
DOI: 10.3389/fvets.2021.708512
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of Fecal Archaea, Bacteria, Eukaryota, and Virus in Przewalski's Horses Following Anthelmintic Treatment

Abstract: Intestinal microbiota is involved in immune response and metabolism of the host. The frequent use of anthelmintic compounds for parasite expulsion causes disturbance to the equine intestinal microbiota. However, most studies were on the effects of such treatment on the intestinal bacterial microbes; none is on the entire microbial community including archaea and eukaryotic and viral community in equine animals. This study is the first to explore the differences of the microbial community composition and struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 103 publications
2
6
0
Order By: Relevance
“…1d ). Consistent with two recent metagenomic studies in horses 30 , 32 , Ascomycota (0.56%) and Basidiomycota (0.25%) were among the top annotated Eukaryota phyla in the gut. At the same time, Saccharomycetaceae represented the dominant eukaryote family 30 .…”
Section: Resultssupporting
confidence: 89%
“…1d ). Consistent with two recent metagenomic studies in horses 30 , 32 , Ascomycota (0.56%) and Basidiomycota (0.25%) were among the top annotated Eukaryota phyla in the gut. At the same time, Saccharomycetaceae represented the dominant eukaryote family 30 .…”
Section: Resultssupporting
confidence: 89%
“…In addition, the lipid metabolism is usually related to the synthesis of dietary lipids and the use of dietary nutrients ( 56 , 57 ). The most identified metabolites produced by microbes through the lipid metabolism confirm our previous assumption that horse botfly infestation can influence the digestive ability of horses ( 37 , 38 ).…”
Section: Resultssupporting
confidence: 84%
“…The previous study by our research group has determined that the horse botfly infestation on E. przewalskii can change some specific bacterial taxa ( 37 ) and also altered the archaea and eukaryotic and viral communities ( 38 ). In addition, the functional analysis showed that the intestinal microbiota mainly participated in the amino acid and carbohydrate metabolism in infected E. przewalskii ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique offers an avenue to understand how the microbiome affects the health and persistence of wildlife animals [24]. To the best of our knowledge, only limited metagenomic analyses of the functional aspects of equid gut microbiota have been reported [25,26].…”
Section: Introductionmentioning
confidence: 99%